2007
DOI: 10.1152/jn.00950.2006
|View full text |Cite
|
Sign up to set email alerts
|

Topological Determinants of Epileptogenesis in Large-Scale Structural and Functional Models of the Dentate Gyrus Derived From Experimental Data

Abstract: In temporal lobe epilepsy, changes in synaptic and intrinsic properties occur on a background of altered network architecture resulting from cell loss and axonal sprouting. Although modeling studies using idealized networks indicated the general importance of network topology in epilepsy, it is unknown whether structural changes that actually take place during epileptogenesis result in hyperexcitability. To answer this question, we built a 1:1 scale structural model of the rat dentate gyrus from published in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
162
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(175 citation statements)
references
References 107 publications
(200 reference statements)
12
162
0
1
Order By: Relevance
“…Nonrandom connectivity features have been discovered in mammalian cortices as well (6)(7)(8)(9)(10). Such networks exhibit high degrees of local clustering with short path lengths [small-world topology (11)(12)(13)], power law distributions of connectivity [scale-free topology (11,13,14)], and nonrandom distributions of connection strengths (8). Additionally, it has been shown that connection probabilities demonstrate fine-scale specificity that depends both on neuronal type and the presence or absence of other connections in the network (15,16).…”
mentioning
confidence: 99%
“…Nonrandom connectivity features have been discovered in mammalian cortices as well (6)(7)(8)(9)(10). Such networks exhibit high degrees of local clustering with short path lengths [small-world topology (11)(12)(13)], power law distributions of connectivity [scale-free topology (11,13,14)], and nonrandom distributions of connection strengths (8). Additionally, it has been shown that connection probabilities demonstrate fine-scale specificity that depends both on neuronal type and the presence or absence of other connections in the network (15,16).…”
mentioning
confidence: 99%
“…4,22,23 In Ref. 22, the connection between network connectivity and epilepsy in the hippocampus was investigated by considering small-world networks of three different types of neurons: noisy and leaky integrate-and-fire neurons, stochastic Hodgkin-Huxley cells, and Poisson spike-train cells.…”
Section: Discussionmentioning
confidence: 99%
“…4, a 1:20 functional model of the rat dentate gyrus was constructed to investigate the functional consequences of two types of changes in network architecture that take place concurrently during epileptogenesis: loss of hillar mossy cells and sprouting of granular cell axons. The removal of mossy cells resulted in a massive reduction in the total number of connections, but this effect was to some extent compensated by an increase in local connectivity due to spatially restricted sprouting of granular cell axons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations